Uptaded checklist, historical overview and illustrated guide to the stygobiont Malacostraca (Arthropoda: Crustacea) species of Yucatan (Mexico) - Dorottya Angyal; Nuno Simões; Maite Mascaró (Subterranean Biology, 2020)
This study provides an updated checklist and an illustrated guide to the 17 currently known stygobiont Malacostraca species of the state of Yucatan (Yucatan Peninsula, Mexico). The compilation is based on the individuals collected during our cave-diving expeditions (2016–2019), and, has the purpose of expanding previous knowledge on the taxonomy of these subterranean crustaceans. The identification guide contains drawings of the main diagnostic characters of the species as well as a brief introduction of the relevant malacostracan orders. The information is further complemented with a historic account and timeline of the stygobiont Malacostraca species of the Yucatan Peninsula. This is the first study that provides a unified tool for the morphological identification of these highly endemic species.